Application of Pulse Treatment to Prolong Shelf Life of Fresh Cut Rose (Rosa hybrida) - Shyntia Atica Putri; Dyah Ismoyowati; Mohammad Affan Fajar Fallah (Agroindustrial Journal, 2017)
Fresh cut flower has characteristis such as perishable and short shelf life. Pulse treatment is akind of method that can prolong fresh cut flower’s shelf life. Pulse treatment is a postharvesthandling which is done by soaking the stem of flower into a solution containing nutrients(glucose and sucrose) and germicides. The objectives of this reseacrh were to determine the bestalternatives of pulse treatment and determine shelf life of fresh cut rose flower of eachtreatment. There were 6 alternatives, namely P 1 (5% sucrose+20 mg/l AgNO 3 ), P 2 (150 mg/lAgNO 3 ), P 3 (1,2% sucrose+0,2 mM STS), P 4 (5% sucrose+20 mg/l AgNO 3 +320 mg/l citricacid), P 5 (1,2% sucrose+ 0,2 mM STS+ warm water (40 0 C)), P 6 (5% sucrose+20 mg/lAgNO 3 +320 mg/l citric acid+warm water (40 0 C)). The parameters used for determining shelflife are color of petals (lightness and redness), moisture content, and texture of stem. As results,shelf life of P1 was 8 days, P2 was 6 days, P3 was 4 days, P4 was 6 days, P5 was 5 days, andP6 was 5 days. All of the alternatives gave longer shelf life than control (4 days). The bestalternatives was P1 with 8 days shelf life. Moisture content in that day was 78,313%, texture ofstem was 47,0603 N, lightness was 31,237 and redness was 46,942.